Post-Endodontic Restoration of a Mandibular First Molar with Extensive Coronal Destruction and Separated Instrument: A Case Report: Post-Endodontic Restoration of a Mandibular First Molar - Ria Septina Rusli; Nevi Yanti; Widi Prasetia (Universitas Syiah Kuala, 2025)
The separation of an endodontic instrument during a root canal treatment is a typical endodontic accident. It may impede disinfection efforts, prevent access to the canal's apex, and ultimately compromise the treatment's success. An option to full-crown restorations that is less invasive is indirect cuspal covering, which may be applied in patients who have had their natural teeth severely damaged. A 30-year-old female patient presented with pain in the left mandibular molar region. The restorative material had recently dislodged. The tooth had previously undergone endodontic treatment in 2019. Extensive coronal damage was seen on the mandibular left first molar during the clinical examination. Radiographic imaging revealed apical radiolucency, three separated instrument fragments within the mesial canal, and inadequate obturation of the distal canal. Retreatment was carried out through the following steps: removal of caries and the existing restoration, retrieval of separated instruments using an ultrasonic tip, and establishment of canal patency. Subsequent cleaning and shaping procedures were then performed. For the final restoration, a fiber-reinforced composite base was placed, followed by a zirconia onlay. Prior to attempting removal of the separated instrument, it is essential to carefully assess the clinical situation and evaluate potential risks. In post-endodontic retreatment cases, the use of an indirect cuspal coverage restoration helps preserve remaining tooth structure while effectively restoring lost tissue. This approach not only enhances the tooth’s functional integrity but also offers favorable esthetic outcomes. A successful outcome was achieved in this case study by combining an FRC base with a zirconia onlay.